2016
DOI: 10.1159/000445608
|View full text |Cite
|
Sign up to set email alerts
|

Probucol Protects Endothelial Progenitor Cells Against Oxidized Low-Density Lipoprotein via Suppression of Reactive Oxygen Species Formation In Vivo

Abstract: Background/Aims: Oxidized low-density lipoprotein (ox-LDL) is a major component of hyperlipidemia and contributes to atherosclerosis. Endothelial progenitor cells (EPCs) play an important role in preventing atherosclerosis and notably decreased in hyperlipidemia. Ox-LDL and ox-LDL-related reactive oxygen species (ROS) have deleterious effects on EPCs. Probucol as an antioxidant and anti-inflammatory drug reduces ROS production. The present study was to determine if probucol could protect EPCs from ox-LDL in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 92 publications
1
19
0
Order By: Relevance
“…These suggested that PTPRO played vital roles in the formation of macrophage-derived foam cells. Generally, in ox-LDL induced AS, increased cell apoptosis and oxidative stress of macrophages was the main mechanism [29], so we detected that whether PTPRO functionally affected the cell apoptosis and oxidative stress of macrophages. As the results showed that over-expression of PTPRO resulted in improved cell apoptosis and oxidative stress and depletion of PTPRO reversed these effects.…”
Section: Discussionmentioning
confidence: 99%
“…These suggested that PTPRO played vital roles in the formation of macrophage-derived foam cells. Generally, in ox-LDL induced AS, increased cell apoptosis and oxidative stress of macrophages was the main mechanism [29], so we detected that whether PTPRO functionally affected the cell apoptosis and oxidative stress of macrophages. As the results showed that over-expression of PTPRO resulted in improved cell apoptosis and oxidative stress and depletion of PTPRO reversed these effects.…”
Section: Discussionmentioning
confidence: 99%
“…This feedback implies that enhanced ENaC activity reduces NO production in endothelial cells and that, conversely, a reduction in NO will relieve its inhibitory effects on ENaC activity. ox ‐LDL is a product of chronic oxidative stress; it is also a potent inducer of oxidative stress, as ox‐LDL injections have been shown to increase both bone marrow and blood ROS levels in mice (Zhang et al , ). Importantly, incubation of cultured human aortic endothelial cells with ox‐LDL enhances ROS via the phosphorylation of p66Shc, an important mediator of oxidative stress (Shi et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Probucol is a clinically used lipid-lowering drug with potent antioxidant and anti-inflammatory properties [ 7 ]. Early studies have demonstrated that probucol can attenuate ischemia-reperfusion injury in the kidney, heart, and brain [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%